Extension Dynamics of the Northern Fonualei Rift and Spreading Center and the Southern Mangatolu Triple Junction in the Lau Basin at 16°S. (19th April 2023) - Jegen, A.; Dannowski, A.; Schnabel, M.; Barckhausen, U.; Brandl, P. A.; Riedel, M.; Beniest, A.; Heyde, I.; Hannington, M. D.; Sandhu, A.; Werner, R.; Kopp, H.
Abstract: Due to the complexity of 2D magnetic anomaly maps north of 18°S and the sparsity of seismic data, the tectonic evolution of the northern Lau Basin has not yet been unraveled. We use a multi‐method approach to reconstruct the formation of the basin at ∼16°S by compiling seismic, magnetic, gravimetric and geochemical data along a 185 km‐long crustal transect. We identified a crustal zonation which preserves the level of subduction input at the time of the crust's formation. Paired with the seafloor magnetization, the crustal zonation enabled us to qualitatively approximate the dynamic spreading history of the region. Further assessment of the recent tectonic activity and the degree of tectonic overprinting visible in the crust both suggest a complex tectonic history including a dynamically moving spreading center and the reorganizing of the local magma supply. Comparing the compiled data sets has revealed substantial differences in the opening mechanisms of the two arms of the Overlapping Spreading Center (OSC) that is made up by the northernmost tip of the Fonualei Rift and Spreading Center in the east and the southernmost segment of the Mangatolu Triple Junction in the west. The observed transition from a predominantly tectonic opening mechanism at the eastern OSC arm to a magmatic opening mechanism at the western OSC arm coincides with an equally sharp transition from and strongly subduction influenced crust to a crust with virtually no subduction input. The degree of subduction input alters the geochemical composition, as well as the lithospheric stress response. Plain Language Summary: The opening of back‐arc basins is often described as analogy to mid‐ocean ridge spreading, where the only difference is the force driving the extension. However, the northern Lau Basin is a prime example for the shortcomings of this analogy since its crust preserves an image of its complex tectonic history. The complexity results from the short‐lived nature of zones of active rifting and spreading in the northern Lau Basin, which is very different from the temporally and spatially steady nature of spreading centers at mid‐ocean ridges. The analysis of different methods (wide angle seismic data using ocean bottom seismometers, multi‐channel seismic, magnetic, gravity, and geochemical data) has led us to conclude that the Lau Basin's crust at 15°30–17°20′S was formed by a dynamically changing, both in regard of magma composition and position, extensional system that consists of the Fonualei Rift and Spreading Center and the Mangatolu Triple Junction. Nevertheless, the crustal zonation, formed by the varying subduction influence during its formation, is still preserved and affects the stress response of the crust and thus the present‐day tectonic behavior. Key Points: Oceanic crust in the north‐eastern Lau Basin formed at the now reorganized FRSC‐MTJ system The position and the opening mechanisms of back‐arc basin spreading center's change more dynamically at mid‐ocean ridges Different opening mechanisms at the southern Mangatolu Triple Junction and northern Fonualei Rift Spreading Center despite their proximity